2019
DOI: 10.3390/microorganisms8010035
|View full text |Cite
|
Sign up to set email alerts
|

Hafnia alvei HA4597 Strain Reduces Food Intake and Body Weight Gain and Improves Body Composition, Glucose, and Lipid Metabolism in a Mouse Model of Hyperphagic Obesity

Abstract: Use of new generation probiotics may become an integral part of the prevention and treatment strategies of obesity. The aim of the present study was to test the efficacy of a potential probiotic strain of lactic bacteria Hafnia alvei (H. alvei) HA4597™, in a mouse model of obesity characterized by both hyperphagia and diet-induced adiposity. For this purpose, 10-week-old high-fat-diet (HFD)-fed hyperphagic ob/ob male mice received a daily treatment with 1.4 × 1010 CFU of H. alvei for 38 days. Effects of H. alv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 34 publications
4
28
0
1
Order By: Relevance
“…These results are in line with previous evidence in mouse models and in sillico findings. In a recent study, the administration of a probiotic, Hafnia alvei, a ClpBproducing bacterium reduced fat mass and food intake in ob/ob and after a high-fat diet in mice [12] and also improved their metabolic profile [14]. In this study, the enterobacterial ClpB gene was also tested in sillico analysis of fecal metagenomes from the MetaHIT database [12].…”
Section: Discussionmentioning
confidence: 97%
“…These results are in line with previous evidence in mouse models and in sillico findings. In a recent study, the administration of a probiotic, Hafnia alvei, a ClpBproducing bacterium reduced fat mass and food intake in ob/ob and after a high-fat diet in mice [12] and also improved their metabolic profile [14]. In this study, the enterobacterial ClpB gene was also tested in sillico analysis of fecal metagenomes from the MetaHIT database [12].…”
Section: Discussionmentioning
confidence: 97%
“…The reason for increased ClpB gene and protein expression during host starvation can be related to the need of an increased protein disaggregation function of this chaperon protein during various catabolic processes and enzymatic remodeling aimed at protecting the survival of the bacterial population [34]. Increased ClpB production itself is not pathogenic and can be, instead, health protective [35,36]. It will be of interest to test whether ClpB also may act as a caloric restriction mimetic, i.e., a substance igniting the protective effects of caloric restriction [37].…”
Section: Discussionmentioning
confidence: 99%
“…Scientists have already identified potential therapies that include bacterial components and/or bacterial-derived small molecules to improve health outcomes in metabolic disease (Cani and Delzenne, 2011;Cavalcanti Neto et al, 2018;Gokhale and Bhaduri, 2020;Wallace and Redinbo, 2013). The use of Hafnia alvei HA4597 in the regulation of satiety through the activation of a-MSH and PYY pathways via the secretion of ClpB is one example of a successful probiotic therapy (Fetissov, 2017;Lucas et al, 2019). A placebocontrolled clinical trial demonstrated efficacy of HA4597 in addition to a hypocaloric diet (À20% kcal) in inducing up to 5% weight loss and a significant reduction in hip circumference in humans, as well as increasing feelings of fullness after 3 months of use.…”
Section: Review Disease Diagnosis and Therapeutic Treatmentmentioning
confidence: 99%